ASSESSING THE IMPACT OF PRESIDENTIAL INSTRUCTION NO. 1 OF 2025 ON THE SERVICE CAPACITY OF EL-PDKP AID ORGANIZATION IN DELIVERING LITIGATION AND NON LITIGATION ASSISTANCE TO THE PUBLIC - Aldy Christian Tarigan; Angel Caroline; Hervinna Ayu Patricia Utari; Theresya Cleo Putri; Rio Armanda Agustian (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research examines the implications of Presidential Instruction No. 1 of 2025 on Government Spending Efficiency for the implementation of legal aid services for the poor, with a particular focus on the EL-PDKP Legal Aid Institute. The right to legal aid is a constitutional guarantee, as stipulated in Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia and Law No. 16 of 2011 on Legal Aid, which affirms the state’s obligation to provide access to justice for all citizens without economic discrimination. However, the budget efficiency policy mandated by the Presidential Instruction has resulted in a significant reduction in legal aid funding, including a decrease in EL-PDKP’s budget from IDR 90,000,000 in 2024 to IDR 36,000,000 in 2025. This research employs a juridical-normative and empirical approach to analyze the tension between principles of distributive justice and the state’s constitutional duty to ensure access to justice. It also assesses the consistency of the Presidential policy with higher legal norms. Empirically, the study explores the concrete impact of budget cuts on EL-PDKP’s capacity to provide litigation and non-litigation legal services. The findings are expected to offer policy recommendations that are more responsive to the legal needs of marginalized communities, while reinforcing the welfare state function in realizing social justice and access to justice in Indonesia.